Edible coating in the post-harvest conservation of endemic mangaba (2018)
Brazilian Cerrado is one of the largest biomes in the world and is considered the richest one. Mangaba fruit is representative of this biome, but it is highly perishable. The aim of this study was to evaluate the application of edible coatings on post-harvest mangaba. Fruits with a good appearance and absence of injuries were used. The experiment was done with a factorial scheme (3 treatments × 6 storage periods). After sanitization and drying, the mangabas received the treatments: (1) whey protein coating; (2) corn starch coating; and (3) no coating (control). Trays with the fruits were stored at room temperature (25°C). Mass loss, pH, total soluble solids (TSS), total titratable acidity (TTA), firmness and ascorbic acid levels were evaluated  after 0, 2, 4, 6, 8, and 10 days of storage. The data were evaluated with analysis of variance, Tukey test and regression. The edible coating with whey protein obtained satisfactory results in the conservation of mangaba, showing good results for the TSS/TTA ratio (16) and vitamin C (116 mg/100 g). The coatings influenced the shelf-life and post-harvest characteristics of this fruits, but the coating with whey protein was the most indicated for mangaba.